Antimicrobial resistance: An unrelenting enemy - M, Ameri; L, Suarez; B, Miles; CF, Michie; J, Abdul (Global Journal of Medical and Clinical Case Reports, 2022)
Antimicrobial Resistance (AMR) poses an increasing threat to global public health and is projected to be one of the greatest challenges of healthcare in the future as the costs of healthcare, morbidity, and mortality will increase. AMR is likely to complicate many routine procedures such as elective surgery in the future. Together, healthcare professionals need to be aware of the significance antimicrobial resistance poses and make changes needed to mitigate the danger as a result of one of the most important developments in medicine.